S doped g-C3N5 for highly efficient photocatalytic H2O2 production and PPCPs degradation via directional transfer of electrons - Wang, Wenjuan; Zhou, Nan; Li, Yakun; Zhu, Zhengqiaoruo; Chen, Xiguo; Zhang, Linlin (Journal of environmental chemical engineering, 2023)
g-C3N5 exhibits thermodynamical stability and longer lifetime of photogenerated carriers, making it a subject of considerable interest and widespread utilization in various photocatalytic reactions. Herein, a novel S doped g-C3N5 photocatalyst achieved an impressive photocatalytic H2O2 production rate (3102.2 μM h−1), which is 95.45 times higher than that of g-C3N5. Furthermore, S doped g-C3N5 also has the ability to rapidly photocatalytic degrade SMX within 30 min. This significant enhancement is mainly attributed to the significant increase in oxygen adsorption capacity caused by S doping and the improvement of photogenerated charge carrier separation efficiency. In addition, photogenerated electrons can be directed and driven onto adsorbed O2 via S doping, which are effectively activated to form H2O2. These findings offer valuable insights into the design and synthesis of g-C3N5-based photocatalysts for efficient H2O2 production and degradation of pollutants. •S-C3N5 is synthesized by a facile thermal polymerization method.•S-C3N5 has a larger surface area with abundant oxygen adsorption sites.•S-C3N5 depicts superior SMX photodegradation and H2O2 production.•The e- occupies a vital position in the H2O2 production reaction.